2011
DOI: 10.1007/s11195-011-9200-1
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study: In What Ways Do Women in Turkey Experience a Change in Their Sexuality During Pregnancy?

Abstract: This study has been performed in order to determine the changes that women experience in their sexuality during pregnancy in Turkey. The sample consisted of 336 women. Data were collected using a questionnaire prepared by researchers. Percentages, mean calculations and Chi-square tests were used in statistical analysis of data. Of the women, 41.7% were in the 23-28 age group, and 35.7% of them had received information relating to their sex lives during pregnancy. Of the subjects, 38.1% had always enjoyed sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 23 publications
5
17
0
4
Order By: Relevance
“…[2][3][4][5][6]8,12,15,25 A recent review, including 48 articles, reported that sexual function declined in pregnancy especially in the third trimester. 26 The deep engagement of the fetal head, stress incontinence, hemorrhoids, weight of the partner on the uterus during sexual intercourse, and subluxation of the pubic symphysis and sacroiliac joints are possible mechanisms of decreased sexual function in the third trimester compared with early pregnancy.…”
Section: Pregnancy and Sexuality In Turkish Womenmentioning
confidence: 99%
“…[2][3][4][5][6]8,12,15,25 A recent review, including 48 articles, reported that sexual function declined in pregnancy especially in the third trimester. 26 The deep engagement of the fetal head, stress incontinence, hemorrhoids, weight of the partner on the uterus during sexual intercourse, and subluxation of the pubic symphysis and sacroiliac joints are possible mechanisms of decreased sexual function in the third trimester compared with early pregnancy.…”
Section: Pregnancy and Sexuality In Turkish Womenmentioning
confidence: 99%
“…Moreover, a woman's sexuality is intensely personal and individual (DeJudicibus & McCabe, 2002;Edlin & Golanty, 2012;Erenel, Eroglu, Vural, & Dilbaz, 2011;Sacomori & Cardoso, 2010), and pregnancy and childbirth is a special period in a woman's life. Moreover, a woman's sexuality is intensely personal and individual (DeJudicibus & McCabe, 2002;Edlin & Golanty, 2012;Erenel, Eroglu, Vural, & Dilbaz, 2011;Sacomori & Cardoso, 2010), and pregnancy and childbirth is a special period in a woman's life.…”
mentioning
confidence: 99%
“…There were also 11 studies (19%) referring to a definition of female sexual dysfunction. Among the attributes identified in the definition of concepts, the consistency that this is a change in the cycle of female sexual response was highlighted (5)(6)(13)(14)(15)(35)(36)(37)(38)(39)(40)(41) , although there are authors that mentioned changes only in some phases (Table 1).…”
Section: Resultsmentioning
confidence: 99%